Doing gender in events feminist perspectives in critical event studies - Grabher, Barbara (Routledge critical event studies research series, 2022)
Exploring the relationship between gender and events, this book delivers an ethnographic analysis of the celebration of gender equality in the context of the culture-led event. Drawing upon Critical Event Studies, Anthropology of the Festive, and Gender Studies, this book provides a comprehensive understanding of the entangled, conceptual entities of gender and events. Through a gendered analysis of the culture-led event, Hull UK City of Culture 2017, this work expands epistemological perspectives relevant to the study of events in general and City/ Capital of Culture initiatives in particular. Driven by a feminist, collaborative methodological approach, the book draws on four years of ethnographic, qualitative research in the city of Hull and its celebration of the title, UK City of Culture, in 2017 and provides an in-depth analysis of how audiences engage, performances enact, and infrastructures condition the production of cultures of gender equality in the citywide celebration. This will be a valuable resource for upper-level students and academics in the field of Event Studies, Cultural Policy, Geography, Anthropology and Gender Studies"--